Transforming waste into stability: improving the soft clay soil with polyethylene terephthalate (PET) column as a sustainable solution - Ng Jun Shen; Muzamir Hasan (Journal of Engineering and Applied Science)
Abstract Exploiting the disposal of items like PET plastic in the ground improvement technique is an alternative for cost optimization and waste reduction. Treating the kaolinitic clay with the stone column method is reliable and effective in enhancing the soil-bearing capacity of soil to prevent soil settlement and soil particle dispersion issues. The previous studies only investigated the modification of stone columns through different sustainable materials, like ash materials. Still, there is no exact focus on the direct analysis of the influence of a single PET column. The fundamental geotechnical engineering properties of research materials were investigated beforehand, exploring the suitability of PET plastic for kaolin’s strength enhancement. This research deployed the vibro-replacement approach, in which a specific diameter of 10 mm or 16 mm hollow section was created, penetrating up to 60 mm, 80 mm, or 100 mm on the unreinforced kaolin specimen. The data of relative density and volume of cylindrical shape determine the amount of PET required to fill in the hollow section. Coherently, the effect of applied axial loads on the unreinforced and reinforced kaolin with a single PET column has been examined. The assessment of shear strength parameters has been carried out by executing the unconfined compression test (UCT) on different diameters of PET columns. The varying column designs have been established with different area replacement ratios, height penetration ratios, and volume replacement ratios. The research discovery presented the effectiveness of utilizing a single PET column with 10 mm and 16 mm diameters, with distinct column dimensions reinforcing the shear strength value of up to 56.53% at the optimum penetrating height ratio of 1.0. This research not only accentuates the advantages of PET plastic but also highlights the environmental advantages, formulating for the execution of disposal of PET material in ground restoration.